Supporting Resilient Coastal Economies in Vietnam : Technical Guidance for Implementing Coastal Setback Lines - World Bank (Washington, DC : World Bank, 2022)
Inclusive and environmentally sound sustainable development requires managing natural resources that societies depend on for the long term. In the context of marine and coastal resources which provide an important source of income for large numbers of households and revenue for countries, this implies balancing the economic, social, and environmental dimensions of the use of the natural resources in marine and coastal areas. The term “blue economy” is increasingly being used to describe this balanced approach. For coastal countries such as Vietnam, the importance of its marine economy is well known. The country has used the goods and services provided by the natural assets in its near-shore and coastal areas – including fisheries, mangroves, wetlands, lagoons, and sandy beaches - for tourism, production of seafood, and controlling climate events that cause erosion and weathering. This report focuses on a critical issue related to effective integrated coastal zone management - establishment of coastal setbacks. The purpose of this report is to help operationalize the requirements associated with establishing coastal setbacks. The work focuses on providing practical guidance drawing on experiences in various provinces.